Photonic heterostructure high contrast grating as a novel polarization control and light confinement system in HCG VCSEL - Gebski, M. (2014)
In this paper we present results of computer optical simulations of VCSEL with modified high refractive index contrast grating (HCG) as a top mirror. We consider the HCG of two different designs which determine the lateral aperture. Such HCG mirror provides selective guiding effect. We show that proper design of aperture of HCG results in almost sixfold increase in cavity Q-factor for zero order mode and a discrimination of higher order modes.